Environmental awareness reducing waste at work - Vocam Worldwide Publishing ([East Melbourne, Vic.] : Vocam Worldwide Publishing, 1998)
Designed to help educate people on issues associated with environmental awareness. Assists management and personnel to look at ways of improving their company's environmental performance
VCD format
Keywords: Environmental pollution; Industrial management -- Environmental aspects; Environmental protection